PELATIHAN PEMBUATAN NOMOR POKOK WAJIB PAJAK SECARA ONLINE MELALUI APLIKASI ZOOM BAGI MAHASISWA KOTA BATAM - Wisnu Yuwono; Johny Budiman; Juven Gautama; Hansend Cristoper; Jihadhatul Akbar; Nelson Donglas; Rido Renando; Kevin Antonio; Trio Trio (National Conference for Community Service Project (NaCosPro), 2020)
The purpose of this community service program is to educate the students in Batam that still unfamiliar with NPWP and even do not have NPWP to get NPWP online. The methods used in this activity are Education, training, and consultancy online through Zoom Application for one semester. The results of implementation showed that students become educated and understand the role of NPWP in daily life and how to register it online and 10 students successfully registered and got NPWP.